Stackable independent power switch cell architecture for isolation voltage summation using WBG devices - Carrá, Martín Javier; Tacca, Hernan Emilio; Lipovetzky, José (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Power electronics is a critical driver of innovation in industries like renewable energy, electric vehicles, and consumer electronics. While silicon (Si) devices have been dominant for five decades, escalating demands for higher power density expose limitations in terms of blocking voltage capacity, operational temperature, and switching frequency. Wide band-gap (WBG) materials, such as silicon carbide (SiC) and gallium nitride (GaN), offer compelling alternatives with low input capacitance, reduced losses, and excellent thermal characteristics. In addition, expanding electrical capabilities involves constructing an array of devices, such as series-connected power MOSFETs. This configuration offers advantages like higher blocking voltage, lower conduction losses, and reduced costs. This paper introduces the design of a fast-switching, stackable switching unit cell (SSUC) utilizing SiC MOSFET devices as power components. The SSUC facilitates the creation of versatile compound switches. To protect the power switch from harmful voltages and current spikes, the design incorporates both an active voltage clamp and a snubber with energy recovery. This feature extends the number of stages that can be connected in series. Experiments with a three-stage compound device, successfully tested at 3 kV, validate the practical applicability and flexibility of this concept.